Developing a teaching supplementary worksheet for Morphology Class - Hanifah Hanifah; Widyarini Susilo Putri (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2020)
Morphology is one of the classes that should be joined by English department students. However, the conventional way to measure the students’ understanding seems unsuccessful. A lecturer of morphology class claimed that written exam in every material given in the classroom was less successful and students tend to be extremely bored when they faced the exam. Based on this phenomenon, the researcher and the lecturer came to the idea that students need to have a new method to measure their understanding. In addition, game is used because it is believed that game is an interesting tool to make students more excited so that they will give much attention on the exam. Research and Development design was used to produce the worksheet product. To finish this product, researcher adopted some steps invented by Borg and Gall which covered need analysis, product development, expert validation, revision, try out and revision. There are 11 games compiled in this worksheet product. Each game provides instructions to play the game and material needed. As the result, students stated that this method, using games, met their need in morphology class. DOI: 10.26905/enjourme.v4i2.4148